An Account of Buddhist Teachings on Environment Management: A Literature Review - Weerasinghe, Dhanushka Nuwan (Journal of Advanced Research in English & Education; Vol 9 No 2 (2024): Journal of Advanced Research in English & Education, 2024)
Buddhist teachings offer a profound framework for environmental management that is grounded in principles of interconnectedness, mindfulness, and ethical conduct. This study has been done mainly focusing on a literature review that explains Buddhist teachings on environment management. The literature synthesises key insights from Buddhist texts, contemporary interpretations, and practical applications to highlight how these teachings can inform modern environmental practices. Traditional Buddhist scriptures, such as the Dhammapada, Chulla Wagga, and the Jataka Tales, emphasise the interdependence of all living beings and the moral imperative to act with compassion towards the environment. Contemporary scholars and practitioners have expanded these ideas, proposing that the Buddhist concepts of non-harming (ahimsa) and mindful consumption can guide sustainable living practices. Additionally, Buddhist monastic communities have implemented eco-friendly practices and advocacy, reflecting the practical application of these teachings. This review underscores the relevance of Buddhist ethics in addressing current environmental challenges and suggests pathways for integrating these ancient insights into contemporary environmental management strategies.